Optimalisasi Sektor Agraris (Padi) Berbasis Data Profil Desa dan Mashlahah sebagai Strategi Peningkatan Kesejahteraan Masyarakat Desa Pudak Kec. Kumpeh Ulu Kab. Muaro Jambi : Penelitian - Syarifah Syamilah; Pit Arjuna; Andifa Maulana Syahru Ramadhan; Nur Aisyah; Fadhilah Fadhilah; Husnul Khotimah; Nurul Annisa Adha (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Optimizing the agricultural sector (rice) based on village profile data and mashlahah as a strategy to improve the welfare of the Pudak Village community is carried out using a systematic approach that integrates empirical data and Islamic values. This study utilizes qualitative research methods with descriptive analysis to evaluate existing agrarian potential and design evidence-based policies. Data collection includes field surveys, in-depth interviews with farmers and village leaders, and analysis of village profile documents. The application of mashlahah principles to agricultural resource management ensures environmental sustainability while strengthening local socio-cultural aspects. The analysis results show increased rice production efficiency through optimal resource allocation strategies, social support from the community, and adaptive village policies. This study recommends the development of an integrated village information system with a mashlahah approach as a strategic model for improving welfare in an inclusive and sustainable manner.